English syntax: A grammar for English language professionals - Roderick A Jacobs (Oxford Univ. Press, 1995)
This book presents in a clear and systematic fashion the basic units and processes of English sentence formation. The book incorporates recent advances in theoretical and applied linguistic research, yet remains uniquely accessible, with a minimum technical terminology. The book's special features - detailed chapter summaries, practice exercises with answer key, clear diagrams, and glossary - make it an ideal text for either undergraduate or graduate course